Магнітопружні хвилі в феромагнетиках в околі структурних фазових преходів в ґратці - Bar’yakhtar, V. G.; Danilevich, A. G. (Publishing house "Academperiodika", 2018)
The dispersion laws for coupled magnetoelastic waves in ferromagnets with uniaxial or cubic symmetry have been calculated. The features of obtained dispersion laws in the vicinity of spin-reorientation phase transitions are analyzed. The interaction between elastic and spin waves is shown to depend on the direction of the ferromagnet magnetic moment. The influence of the magnetoelastic interaction on the dispersion law of quasispin waves in the degenerate ground state of a uniaxial “easy plane” ferromagnet is studied. The results of calculations show that the magnetoelastic interaction eliminates the degeneration and leads to the appearance of a magnetoacoustic gap in the ferromagnet spectrum. The behavior of the spectra of coupled magnetoelastic waves in the vicinity of lattice phase transitions, namely, in the vicinity of martensitic phase transformations in materials with the shape memory effect, is analyzed. The obtained results are used to interpret experimental data obtained for the Ni–Mn–Ga alloy. The phenomenon of a drastic decrease of the elastic moduli for this alloy, when approaching the martensitic phase transition point is explained theoretically. It is shown that the inhomogeneous magnetostriction is the main factor affecting the elastic characteristics of the material concerned. A model dissipative function describing the relaxation processes associated with a damping of coupled magnetoelastic waves in ferromagnets with cubic or uniaxial symmetry is developed. It takes the symmetry of a ferromagnet into account and describes both the exchange and relativistic interactions in the crystal.